Πέπη Γαβαλά, Αρχείο Δημητρίου Κ. Σαλβαρά. Αναλυτικό Ευρετήριο, τόμος Β΄ (1832- 1843). Από το Μυστρά στη Σπάρτη, Γ.Α.Κ., Αρχεία Νομού Λακωνίας, αρ. 5, Σπάρτη 2012 - ΛΙΑΤΑ ΕΥΤΥΧΙΑ Δ. (Μνήμων, 2012)
Δεν παρατίθεται περίληψη.